Use of the Quick Medical Reference (QMR) Program as a Tool for Medical Education - Miller, R. A.; Masarie, F. E. (Methods of Information in Medicine, 1989)
The original goal of the INTERNIST-1 project, as formulated in the early 1970s, was to develop an expert consultant program for diagnosis in general internal medicine. By the early 1980s, it was recognized that the most valuable product of the project was its medical knowledge base (KB). The INTERNIST-1/QMR KB comprehensively summarizes information contained in the medical literature regarding diagnosis of disorders seen in internal medicine. The QMR program was developed to enable its users to exploit the contents ofthe INTERNIST-1/ QMR KB in educationally, clinically, and computationally useful ways. Utilizing commonly available microcomputers, the program operates at three levels - as an electronic textbook, as an intermediate level spreadsheet for the combination and exploration of simple diagnostic concepts, and as an expert consultant program. The electronic textbook contains an average of 85 findings and 8 associated disorders relevant to the diagnosis of approximately 600 disorders in internal medicine. Inverting the disease profiles creates extensive differential diagnosis lists for the over 4250 patient findings known to the system. Unlike a standard printed medical textbook, the QMR knowledge base can be manipulated “on the fly” to format displays that match the information needs of users. Preliminary use of the program for education of medical students and medical house officers at several sites has met with an enthusiastic response.
Keywords: Knowledge Bases; Computer-assisted Diagnosis; Computerbased Problem Solving; Computer-assisted Instruction; Microcomputers